Functional co-expression of xenobiotic metabolizing enzymes, rat cytochrome P450 1A1 and UDP-glucuronosyltransferase 1A6, in yeast microsomes - Ikushiro, Shin-ichi; Sahara, Masahiro; Emi, Yoshikazu; Yabusaki, Yoshiyasu; Iyanagi, Takashi (Biochimica et biophysica acta, 2004)
Xenobiotic Phase I and Phase II reactions in hepatocytes occur sequentially and cooperatively during the metabolism of various chemical compounds including drugs. In order to investigate the sequential metabolism of 7-ethoxycoumarin (7EC) as model substrate in vitro, xenobiotic metabolizing enzymes, rat cytochrome P450 1A1 (P450 1A1) and UDP-glucuronosyltransferase 1A6 (UGT1A6) were co-expressed in Saccharomyces cerevisiae AH22. Rat P450 1A1 and yeast NADPH-P450 reductase were expressed on a multicopy plasmid (pGYR1) in the yeast. Rat UGT1A6 cDNA with a yeast alcohol dehydrogenase I promoter and terminator was integrated into yeast chromosomal DNA to achieve the stable expression. Co-expression of P450 1A1 and UGT1A6 in yeast microsomes was confirmed by immunoblot analysis. Protease treatment of the microsomes showed the correct topological orientation of UGT to the membranes. The metabolism of 7EC to 7-hydroxycoumarin (7HC) and its glucuronide in yeast microsomes was analyzed by reverse phase HPLC. In a co-expression system containing 7EC, NADPH and UDP-glucuronic acid, glucuronide formation was detected after a lag phase, following the accumulation of 7HC. In the case of P450 1A1 and UGT1A6, efficient coupling of hydroxylation and glucuronidation in 7EC metabolism was not observed in the co-expression system. This P450 and UGT co-expression system in yeast allows the sequential biotransformation of xenobiotics to be simulated in vitro.